Analisis Hubungan Usia Kehamilan dan Riwayat KPD dengan Kejadian Ketuban Pecah Dini pada Ibu Bersalin di RSUD Dr. Doris Sylvanus Palangka Raya - Meyska Widyandini; Rena Oki Alestari; Lelly Oktarina (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Premature rupture of membranes is declared if it occurs before the delivery process takes place. PROM is one of the causes of infection in mothers, the disease itself is the third cause of death in mothers. This study aims to determine the relationship between gestational age and history of PROM with the incidence of premature rupture of membranes (PROM). This study is an observational analytic with a case-control design. The population of this study was all mothers who gave birth to RSUD dr. Doris Sylvanus Palangka Raya with premature rupture of membranes as many as 225 mothers, and for the control population were all mothers who gave birth without premature rupture of membranes (PROM) at RSUD dr. Doris Sylvanus Palangka Raya. The case sampling technique in this study used the Slovin formula which resulted in 144 samples. The control sample size in this study was in accordance with the variable data studied, amounting to 144 mothers who did not experience PROM. The control sampling technique in this study used a systematic random sampling technique. The dependent variable in this study was PROM and the independent variables were gestational age and history of PROM. Data analysis using SPSS and the statistical test used is Chi-Square. The results showed that there was a relationship between gestational age and the incidence of PROM (p-value=0.048, OR=1.843) and there was a relationship between the history of PROM and the incidence of PROM (p-value=0.024, OR=3.473). So it was concluded that there was a relationship between gestational age and a history of PROM with the incidence of PROM in RSUD dr. doris Sylvanus Palangka Raya. Health promotion efforts are needed regarding the factors causing the incidence of PROM.